A New pH-Responsive Nano Micelle for Enhancing the Effect of a Hydrophobic Bactericidal Agent on Mature Streptococcus mutans Biofilm - Zhang, Meng; Yu, Zhiyi; Lo, Edward Chin Man (Frontiers in Microbiology, 2021)
The bactericidal effect on biofilm is the main challenge currently faced by antibacterial agents. Nanoscale drug-delivery materials can enhance biofilm penetrability and drug bioavailability, and have significant applications in the biomedical field. Dental caries is a typical biofilm-related disease, and the acidification of biofilm pH is closely related to development of dental caries. In this study, a pH-responsive core-shell nano micelle (mPEG-b-PDPA) capable of loading hydrophobic antibacterial agents was synthesized, and characterized, including its ability to deliver antibacterial agents within acidic biofilm. The molecular structure of this diblock copolymer was determined by Hydrogen-1 nuclear magnetic resonance (1H-NMR) and gel permeation chromatography. The characters of the micelles were studied by dynamic light scattering, TEM, pH titration, and drug release detection. It was found that the hydrophilic micelles could deliver bedaquiline, a hydrophobic antibacterial agent on S.mutans, in acidic environments and in mature biofilm. No cytotoxic effect on the periodontal cells was detected within 48h. This pH-responsive micelle, being able to load hydrophobic antibacterial agent, has good clinical application potential in preventing dental caries.